Stress, anxiety, and illness perception in patients experiencing delay in operative care due to the COVID-19 pandemic - Michelle A. Soloff; Trey Keel; Aaron Nizam; Gary L. Goldberg; Antoinette Sakaris; Michael A. Diefenbach; Danielle K. DePeralta; Marina Frimer (Elsevier, 2023)
Background: Amid the height of the COVID-19 pandemic in the US, the US Surgeon General ordered hospitals and healthcare systems to stop all elective surgical procedures. The aim of our study was to evaluate the additional mental health impact of surgical delay on patients awaiting surgery for benign, pre-malignant and malignant conditions within the context of the COVID-19 pandemic. Study design: All patients over the age of 18 awaiting surgery for benign, pre-malignant or malignant conditions within the gynecologic oncology, surgical oncology and colorectal services across Northwell Health were eligible for participation. Upon successful enrollment, participants completed a baseline questionnaire consisting of the Generalized Anxiety Disorder Questionnaire, the Penn State Worry Questionnaire, and Brief-Illness Patient Questionnaire. Results: The surgical delay was considered moderately to extremely concerning by 72 % of survey respondents, with one third indicating the highest (10/10) level of concern. Fifty-five percent of patients with a pre-operatively suspected/confirmed cancer or pre-malignant condition demonstrated mild to severe anxiety in their completion of the GAD-7 scale. The average time awaiting surgery was 117 days (range 8-292); and 63 % of respondents indicated that the delay had a moderate to severe impact on their daily life. Conclusions: Patients awaiting surgery for confirmed, suspected or pre-malignant conditions expressed decreased sense of control and increased levels of distress compared to patients awaiting procedures for benign conditions (p < 0.05, 95 % CI [-2.65, -0.08]). Future research will focus on the effects of COVID-19 related delays in operative care on clinical outcomes, including cancer morbidity and mortality.